Correlation analysis of different asset classes - Čabra, Martin (2025)
The thesis undertakes quantitative analyses of multi-asset management established on two-parameter risk-return theoretical framework, setting the objective to analyze dynamic and time-constant correlations among multiple asset classes with subsequent portfolio optimization. The preliminary work sets forth the foundations of portfolio theory, diversification effects and the CAPM. The second chapter ensues by selection of financial instruments from various asset classes. The application concerns the stock-bond and REIT-equity rolling and inter-class static correlation analyses, culminating in optimization of weight distribution in portfolio construction, minimizing covariance matrix at pre-set mean return target level.